Clinical applications of the areas under ESPVR - Shoucri, Rachad M. (Cardiovascular Diagnosis and Therapy, 2013)
It has long been observed that the use of the ejection fraction (EF) to assess the condition of the heart offers serious limitations (1). It is estimated that half of the patients presenting with symptoms of cardiomyopathies and heart failure (HF) have preserved EF defined as EF >50%. It was shown in (2) that the areas under the end-systolic pressure-volume relation (ESPVR) in the heart ventricles are sensitive indexes to reflect the state of the myocardium, a review of some clinical applications of indexes derived from the ESPVR can be found in (3). An objective of the study by Doyle et al. (4) is precisely to show that areas under the ESPVR, or bivariate combination of areas with another index, can be used as a prognostically useful tool for studying cases of women with suspected myocardial ischemia.